Reflections about Koch’s philosophy (Nóema, 2016)
Anton Friedrich Koch’s philosophy presents two main thesis: the Antinomiethese and the Subjektivitätsthese, with which the philosopher affirms respectively the original antinomic nature of thought and the necessity of a corporeal subject as guarantor of the space and time system. These thesis and their limits are at the centre of the present paper.
Keywords: Theoretical Philosophy; Koch; Subjektivitätsthese; Antinomiethese; Subjectivity; Sini